Venomous bites and stings in the tropical world. - Warrell, D (1993)
Snakes of the families Viperidae and Elapidae are responsible for the high incidence of morbidity and mortality after snake bites in countries of West Africa, the Indian subcontinent, South-East Asia, New Guinea and Latin America. Envenoming can cause local effects, notably tissue necrosis; and systemic effects, including paralysis, haemostatic disturbances, shock, increased capillary permeability, myocardial damage, rhabdomyolysis and acute renal failure. Specific hyperimmune serum (antivenom) is the mainstay of medical treatment for severe envenoming. Ancillary treatments such as assisted ventilation, repletion of circulating volume, renal dialysis and surgical debridement of necrotic tissues are needed in some cases. Scorpion stings are a common medical problem in middle and southern America, North Africa and the Middle East. Vasodilator drugs are important to counter the effects of massive catecholamine release. Bites by spiders and stings by hymenoptera and marine animals are responsible for deaths and morbidity in some tropical countries.